Characterization of squash polysaccharide and the anti-diabetic effect on type 2 diabetic rat revealed by urine metabolomics analysis - Li Liang; Fuming Zhang; Quanhong Li; Baoguo Sun; Yuyu Zhang; Robert J. Linhardt (Food Science and Human Wellness)
The present study reports the structural characteristics of 3 polysaccharide fractions (SPS-F1, SPS- F2 and SPS-F3) isolated and purified from squash. SPS-F1 (molecular weight (Mw) = 12.30 kDa) and SPS-F2 (Mw = 19.40 kDa) were likely to contain HG and RG-I domain of pectic polysaccharide, respectively. SPS-F2 (Mw = 270.4 kDa) was mainly composed of rhamnose, galactose and arabinose. The treatment with SPS decreased body weight gain, glucose and TG levels in type 2 diabetes rats. Besides, 25 differential metabolites were identified based on urinary metabolomics analysis, which are crucial to the anti-diabetic effect of SPS. The regulation of nicotinamide N-oxide, histamine, cis-aconitate, citrate, L-malic acid, 3-(3-hydroxyphenyl) propanoic acid and N-acetyl-L-aspartic acid were mainly associated with energy metabolism, gut microbiota and inflammation. Study of surface plasmon resonance revealed the binding kinetics with galectin-3 (Gal-3) and fibroblast growth factor 2 (FGF2). The KD values of SPS-F2 and SPS-F3 to Gal-3 were 4.97 × 10-3 and 1.48 × 10-3 mol/L, indicating a weak binding affinity. All 3 fractions showed moderate binding to FGF2 and the affinity was SPS-F3 > SPS-F2 > SPS-F1. Thus, the metabolomics and SPR approach were proved to be a promising tool in exploring the anti-diabetes effects of SPS and provided a deep understanding of the mechanisms.